2008
DOI: 10.1159/000112628
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification in Pseudoexfoliation Syndrome

Abstract: Purpose: To compare the incidence of intraoperative and early postoperative complications (IEPC), visual outcomes, and change in intraocular pressure (IOP) between eyes with and without pseudoexfoliation syndrome (PEX) having cataract extraction by phacoemulsification. Material and Method: 800 eyes with PEX and 1,600 eyes without PEX having cataract extraction by phacoemulsification were included in this retrospective study. Evaluated parameters were incidence of IEPC, visual outcomes and change in IOP. χ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 60 publications
2
17
1
Order By: Relevance
“…1,3,4 Cataract surgery was proven to have a beneficial effect on IOP control in glaucoma in earlier reports. [5][6][7][8][9][10][11][12]14,15 A higher reduction of IOP in eyes with higher preoperative IOP was observed by Shingleton et al in their study where they observed 2.7% eyes progressing to XFG after a period of 3 years despite a 2-4 mm Hg reduction of IOP in XFS eyes. 5,6 However, several of the earlier studies compared the outcomes of cataract surgery between pseudoexfoliation syndrome, POAG, and age matched normals.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…1,3,4 Cataract surgery was proven to have a beneficial effect on IOP control in glaucoma in earlier reports. [5][6][7][8][9][10][11][12]14,15 A higher reduction of IOP in eyes with higher preoperative IOP was observed by Shingleton et al in their study where they observed 2.7% eyes progressing to XFG after a period of 3 years despite a 2-4 mm Hg reduction of IOP in XFS eyes. 5,6 However, several of the earlier studies compared the outcomes of cataract surgery between pseudoexfoliation syndrome, POAG, and age matched normals.…”
Section: Discussionmentioning
confidence: 60%
“…5,6 However, several of the earlier studies compared the outcomes of cataract surgery between pseudoexfoliation syndrome, POAG, and age matched normals. [6][7][8][9][10][11][12][13][14][15][16][17] We chose to study the effects of cataract surgery on the diurnal curve in these patients and compare the outcomes in eyes with an open and narrow angle since that may give us an insight as to the possible etiopathologic role of a cataractous lens on the outflow facility and pressure-related pathogenic mechanisms of glaucomatous damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phacoemulsification in PXF eyes is associated with increasd rates of capsular and zonular tears and vitreous loss (Drolsum et al, 1993;Shingleton et al, 2003). On the other hand, recent studies around the world have shown no statistically significant difference in complication rates during phacoemulsification of PXF eyes (Akinci et al, 2008;Dosso et al, 1997;Hyams et al, 2005) than earlier studies that showed up to a 10-fold increase. Phacoemulsification performed by experienced surgeons, in combination with advanced technologies and devices, have decreased the risks.…”
Section: Preoperative Considerationsmentioning
confidence: 90%
“…One study 21 found that although the complications were more frequent in eyes with PXF than in eyes without, the long-term outcomes between the 2 groups were similar. Another study 24 found equal intraoperative complications (in the absence of preoperative phacodonesis or subluxation) except for an increased rate of early postoperative intraocular pressure (IOP) spikes in eyes with PXF. These and other studies focus on features associated with PXF that might place the eye at a higher risk for complications during the course of cataract surgery.…”
mentioning
confidence: 99%